2002
DOI: 10.1161/01.cir.0000014988.66572.2e
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Atherosclerotic Plaque Components With Intravascular Ultrasound Elastography In Vivo

Abstract: Background-Intravascular ultrasound elastography assesses the local strain of the atherosclerotic vessel wall. In the present study, the potential to identify different plaque components in vivo was investigated. Methods and Results-Atherosclerotic external iliac and femoral arteries (nϭ24) of 6 Yucatan pigs were investigated.Before termination, elastographic data were acquired with a 20-MHz Visions catheter. Two frames acquired at end-diastole with a pressure differential of Ϸ4 mm Hg were acquired to obtain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 212 publications
(121 citation statements)
references
References 8 publications
7
113
0
1
Order By: Relevance
“…Ultrasound elastography as an elasticity imaging modality has been extensively validated theoretically and experimentally. [38][39][40][41][42][43][44][45]53 Several of the elastographic studies and related theoretical models focused on articular cartilage. 42,44,45 For example, poroelastography, 44 or elastographic imaging of poroelastic tissues, has Figure 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound elastography as an elasticity imaging modality has been extensively validated theoretically and experimentally. [38][39][40][41][42][43][44][45]53 Several of the elastographic studies and related theoretical models focused on articular cartilage. 42,44,45 For example, poroelastography, 44 or elastographic imaging of poroelastic tissues, has Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Elastography or elasticity imaging has been used to map mechanical responses and calculate material properties by comparing ultrasound or MR images acquired before and after mechanical loading. This technique, developed in the early 1990s as an alternative tool for early tumor detection and diagnosis based on the principle of palpation, 37,38 has been extensively validated and utilized in intravascular and cardiovascular applications in vivo, 39,40 as well as in the guidance of thermal therapy procedures. 41 Elastography has been used to determine both elastic and mechanical properties of tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that different strain values were obtained with intravascular elastography for different plaque components in vitro and in vivo. 15 One aim of the study was to assess the predictive value of IVUS elastography to identify the vulnerable plaque. This study demonstrates that intravascular elastography can accurately diagnose vulnerable plaques, as defined by Davies 12 in vitro with a high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Validation studies in vitro and in vivo have shown that palpography can identify such plaques with high sensitivity and specificity. 10,15 Until now, this method was applied only to the analysis of single cross sections. Because atherosclerosis is a 3D process, the extension of palpography from a 2D to a 3D technique was a necessary prerequisite to its introduction as a potential clinical modality.…”
Section: Discussionmentioning
confidence: 99%